2020
DOI: 10.1002/adfm.202005930
|View full text |Cite
|
Sign up to set email alerts
|

All‐Inorganic CsPbI3 Quantum Dot Solar Cells with Efficiency over 16% by Defect Control

Abstract: All‐inorganic CsPbI3 quantum dots (QDs) have shown great potential in photovoltaic applications. However, their performance has been limited by defects and phase stability. Herein, an anion/cation synergy strategy to improve the structural stability of CsPbI3 QDs and reduce the pivotal iodine vacancy (VI) defect states is proposed. The Zn‐doped CsPbI3 (Zn:CsPbI3) QDs have been successfully synthesized employing ZnI2 as the dopant to provide Zn2+ and extra I−. Theoretical calculations and experimental results d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
124
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(127 citation statements)
references
References 56 publications
(72 reference statements)
3
124
0
Order By: Relevance
“…[21] Several strategies have been reported to improve CsPbI 3 NC's stability, such as doping, small-molecule ligands, and coreshell structure. [22,23] The stability of LED is generally evaluated by T 50 , that is, the elapsed time for devices decaying to 50% of their initial electroluminescence (EL) intensity. Currently, the T 50 values of most of reported red PeLEDs are less than 10 h, which is far behind the commercialized organic LEDs with over 6 × 10 6 h. [24,25] The long-term operational stability of perovskite light-emitting diodes (PeLEDs), especially red PeLEDs with only several hours typically, has always faced great challenges.…”
mentioning
confidence: 99%
“…[21] Several strategies have been reported to improve CsPbI 3 NC's stability, such as doping, small-molecule ligands, and coreshell structure. [22,23] The stability of LED is generally evaluated by T 50 , that is, the elapsed time for devices decaying to 50% of their initial electroluminescence (EL) intensity. Currently, the T 50 values of most of reported red PeLEDs are less than 10 h, which is far behind the commercialized organic LEDs with over 6 × 10 6 h. [24,25] The long-term operational stability of perovskite light-emitting diodes (PeLEDs), especially red PeLEDs with only several hours typically, has always faced great challenges.…”
mentioning
confidence: 99%
“…Recently, Jen and coworkers used ZnI 2 as the dopant in CsPbI 3 QDs and revealed that the doping of Zn 2+ can improve the thermal stability of the device by increasing the formation energy and the Goldschmidt tolerance factor of CsPbI 3 QDs. [ 299 ] Regarding PV devices, several strategies have been reported to solve the degradation issue caused by interfaces, CTLs, and electrodes. For example, the stability of ZnO CTLs can be improved by various types of dopants, such as aluminum, magnesium, and cesium.…”
Section: Stability Of Quantum Dot Photovoltaic Devicesmentioning
confidence: 99%
“…The NC-based device was better in every aspect than the corresponding bulk solar cell; nonetheless, the performance is still far from CsPbI 3 NCs devices, that have achieved an efficiency over 16%. 41 CsSnX 3 nanocrystals (X = Cl, Br, I) CsSnX 3 rod-shaped nanocrystals (quantum rods, QRs) were synthesized using an easy, fast and clean solvothermal method. The advantage of QRs over spherical nanocrystals is that for the same diameter QRs have bigger volumes leading to a higher per-particle absorbance cross-section and, additionally, their elongated shape is supposed to improve charge injection to transport layers, which can improve device performance.…”
Section: Tin-based Perovskitesmentioning
confidence: 99%
“…5 The record for all-inorganic nanocrystal-based PSC is 16.07% obtained with Zn-doped CsPbI 3 NCs. 41 The optimization between energy levels, doping with other elements, or the introduction of stabilizing ligands/ molecules have been essential for the development of devices with greater efficiencies.…”
Section: Introductionmentioning
confidence: 99%